Selayang Pandang Implementasi Metode Pembelajaran Yang Relevan Bagi Pendidikan Anak Usia Dini Ceria Terpadu Wamena Tahun 2016 - Sudiria Hura; Marde Christian Stenly Mawikere (MAGENANG : Jurnal Teologi dan Pendidikan Kristen, 2022)
This article is a study of relevant learning methods for early childhood, especially those that have been applied to early childhood education units (PAUD) which name is Kelompok Belajar, Beriman dan Bermain dan Taman Kanak-Kanak (KBTRI dan TK) Ceria Terpadu Wamena, Papua in 2016. This study was preceded by a theoretical reference on the multifaceted learning methods of early childhood education. Then followed by the results of empirical research. Theoretical references are built through literature studies, while empirical research uses qualitative methods with descriptive types built with participant field observations and unstructured interviews. The results of the study show that various PAUD learning methods have been applied by teachers KBTRI dan TK Ceria Terpadu Wamena to the students they have mentored. Various learning methods are used by teachers in conveying messages or learning materials, both theory and practice to the students they mentor. Thus the use of learning methods in order to help students to receive all the information or messages conveyed by the teachers according to the learning materials they have prepared well.